The influence of socio-demographics background on the driving behavior A short review - N. Q., Radzuan; Mohd Hasnun Ariff, Hassan; Khairil Anwar, Abu Kassim; Ahmad Azad, Ab. Rashid; Intan Suhana, Mohd Razelan; Nur Aqilah, Othman (Society of Automotive Engineers Malaysia, 2021)
Reckless driving behavior might result in a higher risk of an accident. Many factors are known to be the cause of this driving behavior. One of the factors is the socio-demographic background of the driver. This study aims to review currently available literature that investigates the relationship between driving behavior and any known socio-demographic characteristics. The review also focuses on the method used in the data collection as well as the tools used to perform the analysis to correlate the driving behavior and socio-demographic background. The review found that the influence of socio-demographic background on driving behavior study has not been explored in detail especially from the ethnicity point of view. With regards to the data collection, most of the study utilised the self- report survey, in which the targeted respondents are young adults. There are also studies covering all age groups that made use of the Driving Behaviour Questionnaire, data of traffic accidents or police reports, and virtual reality to collect the data. SAS/STAT statistical software package was found to be a popular choice among researchers when analyzing the data. This review concludes that driving behavior study in the multi-racial country for instance in Malaysia should explore further the relationship between driving behavior and socio-demographic background, especially from the ethnic perspective.